TRADISI KABIN NGODHEH DI KALANGAN ETNIS MADURA DI KELURAHAN MENTAYA SEBERANG KECAMATAN SERANAU KABUPATEN KOTAWARINGIN TIMUR - Rohadi, Rohadi (Universitas Nurul Jadid, 2023)
Humans are creatures that interact with humans and other creatures at all times. In life, humans will always need other people, humans can not achieve their desires by themselves. Therefore, it is called humans as social creatures who need others and are needed by others. Humans need each other with other humans of course in positive things. One human being needs someone else to be his life's companion. To support the desire to develop their offspring, of course, through the process of marriage or marriage. Marriage is a life event where the sacred promises between men and women are delivered. In Indonesia, the condition for a person to get married is if a woman has reached the age of 16 (sixteen) years, while for men 19 (nineteen) years this matter is listed in the law on Marriage. Early marriage is a marriage carried out by a pair of teenagers (men and women) who are still less than 20 years old and are not yet physically, physiologically or psychologically mature. Early marriages that occur are generally carried out by teenage girls. The method used in this research is Qualitative Method of Literature Study. Early marriages that occur in women are caused by several factors, namely cultural factors and customs, parental factors, economic factors, educational factors, and factors from within the individual. Early marriages also have an impact, which is the impact on individuals who do it, the impact on their families and on society or the country